2012
DOI: 10.4103/0019-5413.97261
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphism in collagen IX and intervertebral disc disease in the Indian population

Abstract: Background:Symptomatic intervertebral disc degeneration is being recently reported in younger population, questions the basis of its degenerative etiology. Latest evidences show that genetics play a significant role. Collagen IX, an important constituent of disc, is found to be altered in genetically predisposed individuals. Mutations have been reported in COL9A2 and COL9A3 genes, which encode Collagen IX, in Finnish and various other populations. The purpose of the present study is to test the significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
11
1
1
Order By: Relevance
“…A study from India showed higher frequency of collagen 9a2 heterozygosity in those individuals with disc pathology, despite the absence of a similar association for collagen 9a3 [23] which is in contrast with our findings. This difference may be due to an unidentified genomic factor or another biological pathway, which was not addressed in our study; or this may be related geographical variance of the genomic material and influences of different environmental factors over genes.…”
Section: Discussioncontrasting
confidence: 99%
“…A study from India showed higher frequency of collagen 9a2 heterozygosity in those individuals with disc pathology, despite the absence of a similar association for collagen 9a3 [23] which is in contrast with our findings. This difference may be due to an unidentified genomic factor or another biological pathway, which was not addressed in our study; or this may be related geographical variance of the genomic material and influences of different environmental factors over genes.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, several studies have tested the association between the COL9A2 gene and development of intervertebral disc disease in various populations (Annunen et al, 1999;Kales et al, 2004;Virtanen et al, 2007;Rathod et al, 2012;Janeczko et al, 2014). Annunen et al (1999) carried out an investigation involving 157 patients and 174 controls, identifying a COL9A2 genetic mutation that cosegregates with the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Kales et al (2004) reported that a particular polymorphism of COL9A2 is likely to be a less significant susceptibility factor for the development of intervertebral disc disease in Greek and Finnish populations. Moreover, Rathod et al (2012) revealed that COL9A2 gene variation is a cause of this disease in the Indian population. However, Janeczko et al (2014) found no association between COL9A2 polymorphism and risk of intervertebral disc disease.…”
Section: Discussionmentioning
confidence: 99%
“… 29 A similar association between collagen IX polymorphism and disc degeneration was reported in Indian patients earlier by Rathod et al . 33 However there are no studies to the best of our knowledge assessing COL1A1 polymorphism in Indian patients with IVD degeneration.…”
Section: Discussionmentioning
confidence: 99%